Prevalence of Helicobacter pylori infection among asymptomatic children in southeastern Brazil: a cross-sectional study - Carlos, Ana Beatriz Marques; Costa, Vladimir Eliodoro; Kobayasi, Renata; Rodrigues, Maria Aparecida Marchesan (São Paulo Medical Journal, 2022)
BACKGROUND: The prevalence of Helico bacter pylori (H. pylori) infection is decreasing worldwide, but is still high in developing countries. We previously observed an H. pylori infection rate of 52% among children and adolescents with chronic non-ulcer dyspepsia. OBJECTIVE: To investigate the prevalence of H. pylori infection among asymptomatic children living in a single region and to evaluate the risk factors for this infection. DESIGN AND SETTING: Cross-sectional study in which 161 children aged 5-13 years (mean age 7.8 years), at a public school in Botucatu, state of São Paulo, southeastern Brazil, were assessed. METHOD: The children’s H. pylori infection status was determined through the urea breath test and the risk factors for acquisition of the infection were determined based on a sociodemographic questionnaire. RESULTS: The overall prevalence of H. pylori infection was 20.5%: 18.7% among females and 22.2% among males. The results from the sociodemographic survey did not differ between children with and without H. pylori infection. 30.9% of the children had previous records of upper gastrointestinal symptoms, which consisted of H. pylori infection in only 26.5% of these cases. Family histories of gastritis and peptic ulcer disease were found in relation to 50% and 32.3% of the children with H. pylori infection respectively. CONCLUSION: The prevalence of H. pylori infection among asymptomatic children in southeastern Brazil is lower than that recorded among symptomatic children in the same region and similar to the prevalence of H. pylori infection observed in developed countries.